Implementasi Pengendalian Intern Standar Sarbanes-Oxley Act (SOA) Pada Perusahaan Telekomunikasi - Dodi Herviyan Saputra (EKONOMI DAN BISNIS DIGITAL, 2023)
The Sarbaness-Oxley Act (SOA) was issued to protect the interests of investors by creating good corporate governance and accountability within the company. SOA, especially sections 302 and 404, require an annual management report regarding the company's internal control over financial reporting and the management report is the subject to be audited. This study describes the implementation of SOA at PT Telkom, Tbk, because PT Telkom, Tbk is one of the Indonesian companies listed on the stock exchange in the United States (NYSE) so that PT Telkom must comply with SOA as required by the SEC. The research was conducted by comparing SOA theory or standards with SOA practices that occurred at PT Telkom, Tbk. The results of the research show that PT Telkom has implemented SOA provisions. And from the results of research conducted in the Finance Section of PT. Telkom Yogyakarta shows that increased transparency and regulation of the audit industry that encourages the effectiveness and independence of auditors is needed to maintain and increase investor confidence in the capital market. SOA Implementation at PT. Telkom, especially concerning section 302 (Corporate responsibility for financial reports) and section 404 (Management assessment of internal controls) is expected to provide benefits to the company in realizing Good Corporate Governance (GCG). With Good Corporate Governance, the transparency of PT. Telkom as a public company will be even more real